Depleted lithosphere from the mantle wedge beneath Tres Lagos, southern Patagonia, Argentina - Ntaflos, Th. (2007)
Anhydrous spinel lherzolite and harzburgite xenoliths from Tres Lagos, situated inboard of the Volcanic Arc Gap (VAG) in southernmost Patagonia, are samples of a depleted lithospheric mantle and can be divided into two major groups: metasomatized and non-metasomatized. Metasomatized samples, which are the minority, are partly mylonitized and their metasomatism is related to this tectonic process. A group of non-metasomatized samples have enriched whole rock LREE-abundances that are not consistent with the depleted LREE-abundances in their clinopyroxenes. Intergranular host basalt infiltration could be responsible for the whole rock LREE enrichments. Their Sr- and Nd-isotopic ratios have also been affected by host basalt infiltration, whereas their high Sr-isotopic ratios point to subsequent contamination by ground-water and/or Ca-rich surface solutions. Similar contamination is thought to cause the decoupling of Sr- and Nd-isotopes (high Sr- and Nd-isotopic ratios) observed in the non-metasomatized samples with depleted whole rock LREE. A two-stage partial melting process could be responsible for the origin of the Tres Lagos xenoliths. Model calculations have shown that in the first stage, 2% of batch melting took place in the garnet peridotite field and subsequently the residue experienced 2-8% batch melting in the spinel peridotite field. The Tres Lagos peridotites have not been affected by subduction-related metasomatic processes and they could represent an old lithospheric mantle.